Experimental behaviour of hollow reinforced concrete members with inner octagonal steel tube under lateral impact. Issue 15 (November 2019) - Zhao, Hui; Wang, Rui; Hou, Chuanchuan; Zhang, Dongjie
This work investigated the impact performance of hollow reinforced concrete members with inner octagonal steel tube. Experiments on 13 specimens subjected to low-velocity drop weight impact are presented in this article, covering key parameters such as the impact height, boundary condition, axial load ratio and thickness of the inner tube. The dynamic processes, failure patterns, impact force and mid-span deflection histories, and residual mid-span deflections were obtained from the experiments. Flexure-shear was observed as the main failure pattern for all the specimens under impact. It was found that all the key parameters considered had influences on the impact performance of hollow reinforced concrete specimens with inner octagonal steel tube. Effects of these parameters on the impact performance of hollow reinforced concrete members were discussed.